Interaction of C10, C11 and C18 fatty acids with calcite surface as revealed by IR spectroscopy, X-ray diffraction and atomic force microscopy - Benaissa, Belkacem; Bouhenguel, Mustapha; Bouchemma, Ahcene (European Journal of Chemistry, 2016)
The adsorption of C10, C11 and C18 fatty acids from aqueous solution is a phenomenon of major importance in flotation, geochemistry and oceanography. There is an approach that allows identifying the origin of the formation of aggregates of condensed molecules and the filling mechanism of the adsorbed layer. The different homogeneous domains of the surface are filled by decreasing energetic order. The size of different homogeneous domains controls the size of the lamellar aggregates to one layer and two layers for high concentration. Fatty acid adsorption was investigated at the calcite surface by infrared spectroscopy, atomic force microscopy and X-ray diffraction studies. The adsorption process was studied for different fatty acids in acid medium created by phosphoric acid at pH = 4.8-5.0.